Evaluation of Rock Properties Determined from Core and NMR Data: A Case Study on Asmari Carbonate Reservoir - Mehdi Shabani; Sima Ghaffary; Saeed Yarmohammadi (Journal of Petroleum Science and Technology, 2021)
A detailed description of the carbonate reservoir is an important step in preparing a field development plan. An accurate determination of petrophysical parameters and rock characteristics are key parameters in the carbonate reservoir description. The rock properties are traditionally obtained from different techniques such as lab measurement, well logging, well test, etc. In this manuscript, data from core measurements and NMR measurements are analyzed to study the petrophysical properties of Cretaceous carbonate rock from Asmari Formation. First, the pore size, pore system, porosity and permeability are determined from the core measurements and NMR Analysis. Second, the results of core and NMR evaluations are compared, and the reasons for differences are distinguished. Comparison between the porosity values demonstrates that porosity from NMR and helium injection experiments are very similar in which the average porosity is 21.4 % and NMR porosity is 20.68%. Afterwards, pore sizes received from the NMR model show reliable results and match the pore size distribution determined from the MICP experiment. The permeability value is modeled with NMR permeability predicting models, namely Standard Kenyon and Timur-Coates. Adjusted NMR Permeability results are 17.7 (mD) and 18 (mD) for (SDR) and (TC) methods, respectively, and they are consistent with laboratory core permeability results (Kg=22, Kl=19.2, Kw=18.4). The pore throat distributions are also similar for two NMR and core measurement methods. This study shows how NMR analysis could be useful in determining petrophysical parameters. Ultimately, the results for reservoir characteristics of carbonate rock obtained by core and NMR experiments are compared quantitatively and qualitatively.